2016
DOI: 10.3389/fnsys.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Brain Computation Is Organized via Power-of-Two-Based Permutation Logic

Abstract: There is considerable scientific interest in understanding how cell assemblies—the long-presumed computational motif—are organized so that the brain can generate intelligent cognition and flexible behavior. The Theory of Connectivity proposes that the origin of intelligence is rooted in a power-of-two-based permutation logic (N = 2i–1), producing specific-to-general cell-assembly architecture capable of generating specific perceptions and memories, as well as generalized knowledge and flexible actions. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 159 publications
(225 reference statements)
2
28
0
Order By: Relevance
“…Several observations suggest that the brain's basic computational algorithm is indeed organized by the power-of-two-based permutation coding logic. (Xie et al, 2016) David Chalmers, a philosopher at New York University regularly questions the reality that conscious minds perceive. The problem is that any evidence we could ever get would be also simulated…James Gates Jr. pointed out that such a simulation would mean reincarnation was possible-the simulation could always be run again bringing everybody back to life !…”
Section: Discussionmentioning
confidence: 99%
“…Several observations suggest that the brain's basic computational algorithm is indeed organized by the power-of-two-based permutation coding logic. (Xie et al, 2016) David Chalmers, a philosopher at New York University regularly questions the reality that conscious minds perceive. The problem is that any evidence we could ever get would be also simulated…James Gates Jr. pointed out that such a simulation would mean reincarnation was possible-the simulation could always be run again bringing everybody back to life !…”
Section: Discussionmentioning
confidence: 99%
“…Given that internal brain states (such as attention) are known to reduce neuronal variability [59][60][61], it will be highly interesting to investigate whether such regional variations reflect the underlying molecular and cellular differences (e.g., different cholinergic inputs or receptor expression profiles). In coupling with different NMDA receptor compositions across different regions [62][63][64][65][66], such intrinsic statistical characteristics of spiking-time distribution will likely influence not only how spike-timing patterns drive synaptic plasticity [2,3], but also how cell assemblies in various circuits perform neural computation [51,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…We asked whether the excitatory units in the prelimbic region (PrL) of Golden Syrian hamsters would follow the gamma-like spike patterns. As described in our previous study [51], we implanted 64-channel tetrode arrays bilaterally into the PrL region and , mean ± SEM). The goodness-of-fit analysis showed that all PrL excitatory principal cells can be better described by using the gamma distribution models ( Figure 9C, 0 D > for all PrL excitatory principal cells), and D was linearly correlated with the mean firing rates (correlation coefficient is 0.79).…”
Section: Spike-timing Patterns Of Principal Cells In the Hamster Prelmentioning
confidence: 99%
“…Several observations suggest that the brain's basic computational algorithm is indeed organized by the power-of-two-based permutation coding logic (Xie et al, 2016).…”
Section: Examples Of the Qee Codesmentioning
confidence: 99%